The limits of bodies: Gatherings and the problem of collective presence. Issue 2 (12th April 2022) - Zuckerman, Charles H. P.; Mathias, John
Abstract: Modern social collectivities—such as nations, publics, and political movements—depend upon the capacity of media technologies to transcend bodily proximity. The contemporary proliferation of such remote sociality may seem to render physical gatherings superfluous. But at times, people go to great pains to manifest collectivities by assembling bodies in one place. This article explores what we should make of cases in which it is not enough for collectivities to be projected, abstracted, imagined, or invoked—times when bodies together are all that will do. Presenting research from India and Laos, and in dialogue with reflections on the COVID‐19 pandemic, we consider those cases in which bodies are thought to be essential for making collectivities. We show that it is the limits and weaknesses of bodies—that they require sleep and food, that they are vulnerable to police batons and thrown stones, that they can usually only be in one place at a time—that often make them potent materials for building mass actors. Sketching a comparative anthropology of gathering, we reflect on what these limits afford and rethink what bodies might mean for future modes of social connection. Resumen: Las colectividades sociales modernas –tales como naciones, públicos, movimientos políticos– dependen de la capacidad de las tecnologías de los medios para trascender la proximidad corporal. La proliferación contemporánea de tal sociabilidad remota puede parecer que hace las reuniones sociales superfluas. Pero a veces, las personas hacen un gran esfuerzo para manifestar colectividades al ensamblar cuerpos en un lugar. Este artículo explora qué deberíamos hacer con los casos en los cuales no es suficiente para las colectividades ser proyectadas, abstraídas, imaginadas o invocadas –momentos en que cuerpos juntos es todo lo que las harán. Al presentar investigación de India y Laos, y en diálogo con reflexiones sobre la pandemia del COVID‐19, consideramos esos casos en los que se piensa que los cuerpos son esenciales para hacer colectividades. Mostramos que son las limitaciones y debilidades de los cuerpos –que ellos requieren dormir y alimento, que ellos son vulnerables a los bolillos de la policía y las piedras arrojadas, que usualmente solo pueden estar en un lugar a la vez– que a menudo los hace materiales potentes para construir actores de masa. Al bosquejar una antropología comparativa del concurrir, reflexionamos sobre lo que estos límites permiten y repensamos lo que los cuerpos podrían significar para modos de conexión social futuros. [ cuerpo, copresencia, presencia, colectividad social, semiótica, activismo, protestas, funerales, COVID‐19, India, Laos ]